2020
DOI: 10.1177/0042085920923011
|View full text |Cite
|
Sign up to set email alerts
|

Charter School Regulation as a Disproportionate Barrier to Entry

Abstract: In response to concerns regarding school quality, state policy-makers reformed their charter school authorization processes to impose greater regulatory barriers to chartering. These barriers to market entry could impose substantial burdens for Black and Latino would-be charter operators, as well as independent operators, who may lack access to social and financial capital. We test these hypotheses by comparing application outcomes from states with high and low levels of charter regulation, as measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…For instance, those applicants with neoliberal/no-excuses perspectives often operated from deficit-based assumptions and located change within the individual student without an analysis of structural conditions, at times blaming students and their families for educational disparities, while communitarian approaches often explored structural inequity, community uplift, and culturally relevant approaches to teaching. Following this research, scholars have begun to pay attention to these racial disparities in authorizing (Kingsbury et al, in press).…”
Section: Charter School Authorization Process: a Ritual Of Stratificamentioning
confidence: 99%
“…For instance, those applicants with neoliberal/no-excuses perspectives often operated from deficit-based assumptions and located change within the individual student without an analysis of structural conditions, at times blaming students and their families for educational disparities, while communitarian approaches often explored structural inequity, community uplift, and culturally relevant approaches to teaching. Following this research, scholars have begun to pay attention to these racial disparities in authorizing (Kingsbury et al, in press).…”
Section: Charter School Authorization Process: a Ritual Of Stratificamentioning
confidence: 99%
“…In a study of authorization in Louisiana, researchers found that authorizers engaged in colorblind assessments of charter petitions, yielding a paucity of petitions granted to community-based and Black-led schools in favor of those that reified marketized, racialized logics, which are often espoused by prominent CMOs (Henry & Dixson, 2016). A recent study found similar findings in comparing authorization processes and application outcomes among states with stricter or more lenient regulation, noting how greater regulatory measures negatively affected Black and Latinx applicants as well as those from independent charters (Kingsbury et al, 2020).…”
Section: Cmo Politicsmentioning
confidence: 85%
“…Given that the focus of our study is on the most preliminary steps in the authorizing process and the opening of an effective and equitable charter school, we believe that future research should be done that interrogates how authorizers may or may not be involved in the operations of opened charter schools. Our study also neither addresses how the requirement for submitting charter applications themselves may serve as a barrier to entering the charter market (Kingsbury et al, 2020; McShane et al, 2015) nor does it look further down the charter authorization process to determine the extent to which proposed practices become reality.…”
Section: Discussionmentioning
confidence: 96%